Indonesia's role as a non-permanent member of the UN Security Council in Assisting the Resolution of Conflict in Afghanistan for the 2019-2020 Period - Khoirunnisa Jubaidi; Maisarti Razali Budiman (Ilomata International Journal of Social Science, 2021)
Indonesia has been elected for the fourth time to become a non-permanent member of the UN Security Council. Indonesia with its free and active foreign policy is entrusted with this position. Indonesia will serve during the 2019-2020 period. Indonesia has done a lot for world peace in accordance with the 1945 Constitution and with its free and active political principles. The author wants to see the role of Indonesia in its membership in the UNSC in helping to bring about peace in conflicting countries, in this case Afghanistan. However, the long conflict between the United States and the Taliban can be contained and resolved properly. The UN Security Council has the responsibility for this, and Indonesia takes part in it. How Indonesia makes policies and takes a role as a member of the International Organization Agency, who has this sizeable responsibility. By using the theory of Conflict Resolution and international organizations as an analysis tool, the author will discuss Indonesia's role as a non-permanent member of the UN Security Council in resolving the conflict in Afghanistan in 2019-2020. Keywords: Role, conflict, Peace